THE INFLUENCE OF SOCIAL CAPITAL AND INTERPERSONAL RELATIONSHIP TOWARD ORGANIZATIONAL CITIZENSHIP BEHAVIOR AT JAMKRINDO MANADO - Wuisan, Adelina Regina; Pangemanan, Sifrid . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: The conditions above imply that potential human resources are capable to adopt the progress and development of science and technology to always growth. This requires employees to achieve performance which as high as possible with the hope of the organization or company can compete and competitive in the era of globalization today. The purpose of this research is to find the impact of variables toward organizational citizenship behavior in Jamkrindo Manado. This research used quantitaitve method. The sample of this research is employee of Jamkrindo Manado. This research used purposive sampling and the date filled by the questionaire. The result of this research is the social capital, interpersonal relationshipsignificant influence on organizational citizenship behavior simultaneously. social capital has no significant influence toward organizational citizenship behavior in jamkrindo manado partially. interpersonal relationship behavior has significant influence toward organizational citizenship behaviorin jamkrindo manado partially. Recommendation is Jamkrindo Manado should focus more on know what drives interpersonal relationship in Jamkrindo Manado have effect on OCB in the office. Jamkrindo Manado should make company meetings that enhance OCB in the office.Â Keywords: organizational citizenship behavior